THE STUDENTS’ MATHEMATICAL UNDERSTANDING ABILITY THROUGH SCIENTIFIC-ASSISTED APPROACH OF GEOGEBRA SOFTWARE - Euis Eti Rohaeti; Martin Bernard (IKIP Siliwangi and I-MES, 2018)
This research is motivated by the low ability of mathematics understanding of junior high school students, with the aim of the study is to examine the achievement, improvement, implementation, and difficulty of mathematics understanding ability of junior high school students through learning using Geogebra-assisted scientific approach. The method of this research is an experimental method with two class groups namely experimental class and control class. The population of this research is all junior high school in West Bandung Regency, randomly selected and selected SMP Krida Utama Padalarang. Samples were taken randomly class VIII chosen D as an experimental class, and class VIII C as control class. The experimental level received learning with the Geogebra-assisted scientific approach, and the control class gained regular learning. The results showed that the achievement and improvement of the ability of mathematical understanding between students who received learning with scientific approach assisted Geogebra software better with students who get regular learning. Learning with Geogebra-assisted scientific approach can be implemented in the experimental class by the steps of the scientific method of observing, asking, exploring, associating, and communicating.